Startups: An Initial Step for Algerian Entrepreneurial Universities - Wassila SAOUD (European Journal of Management Issues)
Purpose: The study aimed to evaluate Algerian universities' success in becoming entrepreneurial, focusing on their effectiveness in encouraging students to establish startups as an initial step toward this transformation.